Major Depression and Coronary Artery Disease in the Swedish Twin Registry: Phenotypic, Genetic, and Environmental Sources of Comorbidity - Kendler, Kenneth S. (2009)
CONTEXT: Major depresssion (MD) and coronary artery disease (CAD) frequently co-occur. The mechanisms of comorbidity are uncertain. OBJECTIVE: To clarify sources of MD-CAD comorbidity. DESIGN: Major depression was assessed at the time of the personal interview, and CAD from hospital discharge records and death certificates. SETTING: Swedish population-based twin registry. PARTICIPANTS: The study included 30 374 twins with a mean age of 57 years. MAIN OUTCOME MEASURE: Modified DSM-IV diagnosis of MD or diagnosis of CAD. RESULTS: Lifetime association between MD and CAD was modest (odds ratio, ~1.3). In time-dependent Cox analyses, onset of CAD produced concurrent and ongoing hazard ratios for MD of 2.83 and 1.75. These risks increased if the diagnosis of CAD was restricted to myocardial infarction. Onset of MD increased the concurrent and ongoing hazard ratios for CAD to 2.53 and 1.17. The ongoing CAD risk was strongly associated with depressive severity and recurrence. Twin models showed that the modest comorbidity between MD and CAD in women arose primarily from shared genetic effects, although the genetic correlation was small (+0.16). In men, the source of comorbidity was moderated by age, being environmental in older members and largely genetic in younger members of the sample. CONCLUSIONS: Although the MD-CAD relationship across the lifespan is modest, time-dependent models reveal stronger associations. The sustained effect of CAD onset on MD risk is much stronger than vice versa. The effect of MD on CAD is largely acute, and the longer-term effects are apparently mediated via depressive recurrence. When examined separately, in men, environmental effects, which are often acute, play a large role in MD-CAD comorbidity, whereas in women, chronic effects, which are in part genetic, are more important. In men, genetic sources of MD-CAD comorbidity are more important in younger members of the sample.